Planning the Sustainable Spatial Development of Mountain Tourism in Europe and Serbia / Dragiša Dabić - Maksin, Marija (Arhitektura i urbanizam, 2022)
ског туризма у Србији.
Keywords: planning; sustainable development; mountain tourism; Europe; Serbia